Learning across views for stereo image completion. Issue 7 (14th October 2020) - Ma, Wei; Zheng, Mana; Ma, Wenguang; Xu, Shibiao; Zhang, Xiaopeng
Abstract : Stereo image completion (SIC) is to fill holes existing in a pair of stereo images. SIC is more complicated than single image repairing, which needs to complete the pair of images while keeping their stereoscopic consistency. In recent years, deep learning has been introduced into single image repairing but seldom used for SIC. The authors present a novel deep learning‐based approach for SIC. In their method, an X‐shaped fully convolutional network (called SICNet) is proposed and designed to complete stereo images, which is composed of two branches of convolutional neural network layers to encode the context of the left and right images separately, a fusion module for stereo‐interactive completion, and two branches of decoders to produce completed left and right images, respectively. In consideration of both inter‐view and intra‐view cues, they introduce auxiliary networks and define comprehensive losses to train SICNet to perform single‐view coherent and cross‐view consistent completion simultaneously. Extensive experiments are conducted to show the state‐of‐the‐art performances of the proposed approach and its key components.